Perceptions of Auditors' Independence: An Empirical Analysis. - Shockley, Randolph A. (The Accounting Review, 1981)
ABSTRACT: Recent challenges of the audit independence assumption have impelled the accounting profession to consider ways of improving the credibility of audit reports. This study examines the perceived effects of competition, MAS, audit-firm size, and tenure on the risk that audit Independence may become impaired. Factorial analysis of variance techniques are used to analyze judgments obtained in an experimental task from four subject groups (a) Big Eight partners, (2) partners from local and regional CPA firms, (3) commercial loan officers, and (4) financial analysts Results indicate that audit firms operating in highly competitive environments, firms providing MAS, and smaller audit firms are perceived as having a higher risk of losing independence. An audit firm's tenure with a given client is not significant. Though perceptual differences exist between the groups, an overall analysis ranks competition as the most important factor, followed by audit-firm size and MAS.